2019
DOI: 10.1186/s12935-019-1075-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia promotes Snail-induced epithelial–mesenchymal transition of gastric cancer via activating ENO1 expression

Abstract: Background: Gastric cancer (GC) is one of the most common gastrointestinal malignancies worldwide. Emerging evidence indicates that hyperglycemia promotes tumor progression, especially the processes of migration, invasion and epithelial-mesenchymal transition (EMT). However, the underlying mechanisms of GC remain unclear. Method: Data from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases were used to detect the expression of glycolysis-related enzymes and EMT-related transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…Previous studies found that the upregulation of ENO1 was positively correlated with progression and poor prognosis in breast cancer, prostate cancer, thyroid carcinoma, hepatocellular carcinoma, cholangiocarcinoma, neuroblastoma, neuroendocrine tumors, lung cancer, and pancreatic cancer ( 4 , 9 13 ). Consistent to previous studies ( 2 , 4 , 14 23 ), more details are summarized in Supplementary Table 1 . Additionally, increased ENO1 expression has been observed in different types of drug-resistant cancer cells, suggesting the potential use of ENO1 as a biomarker for drug resistance and as a target for cancer therapy ( 5 ).…”
Section: Introductionsupporting
confidence: 66%
“…Previous studies found that the upregulation of ENO1 was positively correlated with progression and poor prognosis in breast cancer, prostate cancer, thyroid carcinoma, hepatocellular carcinoma, cholangiocarcinoma, neuroblastoma, neuroendocrine tumors, lung cancer, and pancreatic cancer ( 4 , 9 13 ). Consistent to previous studies ( 2 , 4 , 14 23 ), more details are summarized in Supplementary Table 1 . Additionally, increased ENO1 expression has been observed in different types of drug-resistant cancer cells, suggesting the potential use of ENO1 as a biomarker for drug resistance and as a target for cancer therapy ( 5 ).…”
Section: Introductionsupporting
confidence: 66%
“…vital role of ENO1 as an oncogene that promotes tumor progression. Emerging data indicate that ENO1 silencing inhibits tumor cell proliferation and invasion and reverses EMT progression [60][61][62][63] . In our study, we investigated HCC growth and metastasis in the presence and absence of ENO1.…”
Section: Discussionmentioning
confidence: 99%
“…These data correlated well with previous observations in lung cancer 25 , pancreatic cancer 26 , and colorectal cancer 59 , again supporting the vital role of ENO1 as an oncogene that promotes tumor progression. Emerging data indicate that ENO1 silencing inhibits tumor cell proliferation and invasion and reverses EMT progression 60 63 . In our study, we investigated HCC growth and metastasis in the presence and absence of ENO1.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-enolase is overexpressed in multiple human cancer types, contributing to increased glycolysis and tumor growth ( Altenberg and Greulich, 2004 ; Chang et al, 2006 ; He et al, 2007 ; Tsai et al, 2010 ; Capello et al, 2011 ; Song et al, 2014 ; Fu et al, 2015 ; Sun et al, 2017 , 2019 ; Zhan et al, 2017 ; Yin et al, 2018 ; Zhang et al, 2018 , 2020 ; Cheng et al, 2019 ; Ji et al, 2019 ; Qiao et al, 2019 ; Xu et al, 2019 ; Chen et al, 2020 ). ENO1 overexpression is often associated with anti-ENO1 autoantibody responses and may have prognostic and diagnostic value in certain cancers ( Table 1 ; Adamus et al, 1998 ; Tomaino et al, 2011 ; Pranay et al, 2013 ; Hsiao et al, 2015 ; Griggio et al, 2017 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%